GPR68 Contributes to Persistent Acidosis-Induced Activation of AGC Kinases and Tyrosine Phosphorylation in Organotypic Hippocampal Slices - Zhou, Guokun; Zha, Xiang-ming (Frontiers in Neuroscience, 2021)
Persistent acidosis occurs in ischemia and multiple neurological diseases. In previous studies, acidic stimulation leads to rapid increase in intracellular calcium in neurons. However, it remains largely unclear how a prolonged acidosis alters neuronal signaling. In our previous study, we found that GPR68-mediated PKC activities are protective against acidosis-induced injury in cortical slices. Here, we first asked whether the same principle holds true in organotypic hippocampal slices. Our data showed that 1-hr pH 6 induced PKC phosphorylation in a GPR68-dependent manner. Go6983, a PKC inhibitor worsened acidosis-induced neuronal injury in wild type (WT) but had no effect in GPR68-/- slices. Next, to gain greater insights into acid signaling in brain tissue, we treated organotypic hippocampal slices with pH 6 for 1-hr and performed a kinome profiling analysis by Western blot. Acidosis had little effect on cyclin-dependent kinase (CDK) or casein kinase 2 activity, two members of the CMGC family, or Ataxia telangiectasia mutated (ATM)/ATM and RAD3-related (ATR) activity, but reduced the phosphorylation of MAPK/CDK substrates. In contrast, acidosis induced the activation of CaMKIIα, PKA, and Akt. Besides these serine/threonine kinases, acidosis also induced tyrosine phosphorylation. Since GPR68 is widely expressed in brain neurons, we asked whether GPR68 contributes to acidosis-induced signaling. Deleting GPR68 had no effect on acidosis-induced CaMKII phosphorylation, attenuated that of phospho-Akt and phospho-PKA substrates, while abolishing acidosis-induced tyrosine phosphorylation. These data demonstrate that prolonged acidosis activates a network of signaling cascades, mediated by AGC kinases, CaMKII, and tyrosine kinases. GPR68 is the primary mediator for acidosis-induced activation of PKC and tyrosine phosphorylation, while both GPR68-dependent and -independent mechanisms contribute to the activation of PKA and Akt.